Heritage Tourism in Bali: An Analysis of Sustainable Tourism Development Policies - I Gede Widyastana Putra; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Heritage tourism is one of the main pillars of tourism development in Bali, oriented not only toward economic growth but also toward the preservation of cultural, social, and environmental values. This study aims to analyze the management of heritage tourism in Bali from a Public Administration perspective, focusing on the role of local government in policy formulation, inter-actor coordination, and public value creation. This research employs a qualitative approach through literature review and policy analysis. The theoretical framework is based on the concepts of Good Governance, New Public Service, Collaborative Governance, and Public Value. The findings indicate that the success of heritage tourism management in Bali is highly dependent on transparent, participatory, and accountable governance, as well as collaboration among government institutions, traditional communities, the private sector, and other stakeholders. The government’s role extends beyond regulation to include facilitation and mediation in balancing economic interests with cultural preservation. This study concludes that public value oriented heritage tourism management can support sustainable tourism development and strengthen Bali’s cultural identity. Keywords: Heritage Tourism, Public Administration, Governance, Public Value, Bali.